Pullout behavior of steel fibers with different shapes from ultra-high performance concrete (UHPC) prepared with granite powder under different curing conditions. (30th June 2019) - Zhang, Hongru; Ji, Tao; Lin, Xiaoying
Highlights: Quartz powder (QP) was replaced by granite powder (GP) to prepare UHPC. The matrix strength and fiber/matrix bonds are enhanced by the incorporation of GP. Thermal curing improves the fiber/matrix bonds but also increases the brittleness. Excessively deformed fibers have the risk to fracture through pullout. Effects on fiber/matrix bonds should consider both curing and fiber shapes. Abstract: Granite powder (GP) was used to completely replace quartz powder (QP) as the fine filler to prepare ultra-high performance concrete (UHPC). Pullout behavior of steel fibers from the target UHPC, i.e., UGP, was investigated by a single-fiber pullout test and was compared to the control concrete. The influence of the fiber shape and the curing conditions with different thermal treatments on the pullout resistance from UGP was discussed. It is found that the replacement of QP by GP can improve the pore structure and the density of the cement matrix. As a result, the compressive and flexural strengths of UHPC are enhanced; meanwhile, the pullout resistance with the straight & smooth (S) fiber is also enhanced. Compared to standard curing (SC), warm water curing (WWC) and autoclaved curing (AC) can improve the peak pullout load, the average bond strength, the pullout energy and the fiber utilization rate of the S fiber and most deformed fibers, but the brittleness of failure by fiber fracture also increases. Deformed fibers demonstrate superior pullout resistance compared to the S fiber, however, the excessively deformed fibers (e.g, the more corrugated C2 fiber with dense waves) tend to fracture when the cement matrix cured under WWC and AC presents ultra-high strength. It is suggested that it should be feasible to prepare UHPC by replacing QP with GP, but the effects of curing and the fiber shape on the pullout resistance from UGP should be comprehensively considered. The appropriate fibers employed by UGP in practical use should be determined according to the curing to be provided.